2014
DOI: 10.1002/hbm.22645
|View full text |Cite
|
Sign up to set email alerts
|

Parcellation of the human orbitofrontal cortex based on gray matter volume covariance

Abstract: The human orbitofrontal cortex (OFC) is an enigmatic brain region that cannot be parcellated reliably using diffusional and functional magnetic resonance imaging (fMRI) because there is signal dropout that results from an inherent defect in imaging techniques. We hypothesise that the OFC can be reliably parcellated into subregions based on gray matter volume (GMV) covariance patterns that are derived from artefact-free structural images. A total of 321 healthy young subjects were examined by high-resolution st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…However, those commonly used fMRI and probabilistic tractography connectivity‐based parcellation approaches, may not be optimal for small‐sized structures like the hippocampus, due to their low spatial resolution. Inspired by the parcellation of insula (Kelly et al, ) and orbitofrontal cortex (Liu et al, ) with GMV covariance, we parcellated the human hippocampus based on this technique which emerged from high‐resolution structural images (Mechelli et al, ). GMV covariance examines covariation of gray matter morphology between brain regions across populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, those commonly used fMRI and probabilistic tractography connectivity‐based parcellation approaches, may not be optimal for small‐sized structures like the hippocampus, due to their low spatial resolution. Inspired by the parcellation of insula (Kelly et al, ) and orbitofrontal cortex (Liu et al, ) with GMV covariance, we parcellated the human hippocampus based on this technique which emerged from high‐resolution structural images (Mechelli et al, ). GMV covariance examines covariation of gray matter morphology between brain regions across populations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that GMV covariance recapitulates functional brain networks (Seeley, Crawford, Zhou, Miller, & Greicius, ) and the pattern of interregional structural covariance is akin to the pattern of functional connectivity (Alexander‐Bloch, Giedd, & Bullmore, ), thereby driving the brain functioning in an efficient way. GMV covariance has been used to reliably parcellate brain regions such as the insula (Kelly et al, ) or the orbitofrontal cortex (Liu, Qin, Qi, Jiang, & Yu, ). These two studies (Kelly et al, ; Liu et al, ) employed GMV correlation (GMVCorr), which is a bivariate voxel‐to‐voxel correlation method that utilizes second‐order statistics to depict the association of the GMV between two voxels within the region of interest (ROI).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional analyses of the lateral OFC revealed that this region is involved in the processing of gustatory, olfactory or somatosensory rewarding stimuli but also the processing of emotional punishments, evaluating and updating the emotional status, maintaining social behavior, active retrieval of information, semantic processing, verb generation, processing of stimuli that have a coherent temporal structure, music listening, assigning value to certain things and events and decision-making (Papathanassiou et al, 2000;Levitin and Menon, 2003;Kringelbach and Rolls, 2004;Petrides, 2005;Campbell-Meiklejohn et al, 2012;Alluri et al, 2013;Liu et al, 2015;Neubert et al, 2015;Rolls et al, 2015;Hirose et al, 2016). Tasks that require quick responses while retrieving information from the long-term and working memory also showed activations in the lateral OFC.…”
Section: Introductionmentioning
confidence: 99%